Seeing tongues, hearing scripts : orality and representation in the ancient novel - Rimell, Victoria (Ancient narrative. Supplementum, 2007)
The Greek and Roman novels can be seen as an important transitional moment in the trajectory from performance to reading, from oralism to textuality, that has underpinned the history of discourse in European consciousness since the 5th century BC. In different and intriguing ways, they explore the contrast, tension, conflict, competition or dialogue between modes of discourse, which frame the novel's concern with identity and self-fashioning, as well as advertising innovation more generally. This volume brings together an international group of scholars interested in ancient and modern construc.